2019
DOI: 10.1177/2158244019898247
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Expected Income on Wealth Accumulation and Retirement Contribution of Thai Wageworkers

Abstract: Thailand has now become the aging society. However, the fact that the majority of Thai wageworkers do not effectively save for their retirement may result in several elderly living below the poverty threshold during retirement. The objectives of this research article were to find the factors determining Thai wageworkers’ retirement contribution. Founded on the theory of life-cycle hypothesis, this article employed a sample of 300 wageworkers in the Northeast of Thailand and performed a statistical analysis usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Wealth accumulation was the essential factor allowing a wageworker to contribute to retirement effectively in the long term (C. Ketkaew et al, 2019c). Insufficient wealth accumulation resulted from low financial attainment capacity (C. Ketkaew et al, 2020Ketkaew et al, , 2019b) may cause financial insecurity.…”
Section: Financial Insecuritymentioning
confidence: 99%
“…Wealth accumulation was the essential factor allowing a wageworker to contribute to retirement effectively in the long term (C. Ketkaew et al, 2019c). Insufficient wealth accumulation resulted from low financial attainment capacity (C. Ketkaew et al, 2020Ketkaew et al, , 2019b) may cause financial insecurity.…”
Section: Financial Insecuritymentioning
confidence: 99%
“…Ideally, the number of clusters should be between ten and fifteen to ensure that clusters are sufficiently wide to sort a significant number of codes (Morse and Field 1995). Moreover, note that we decided to use the age of 35 as a cut-off for analyzing the segments because most Thai individuals start to save and accumulate long-term assets around the age of 30 to 35 (Ketkaew et al 2019c).…”
Section: Discussionmentioning
confidence: 99%
“…After a thorough review of the pilot test, the researchers configured the questions to guide each question into specific topics for the respondents to answer (see Appendix A). The questions were adapted from Ketkaew et al (2019c) and merged with concepts suggested by Cooper and Vlaskovits (2016). The framework used for the in-depth interview includes the customer zoom tool, the problem zoom tool, and the solution zoom tool (Cooper and Vlaskovits 2016).…”
Section: Research Design and Samplementioning
confidence: 99%
See 1 more Smart Citation
“…The data's descriptive statistics were first analyzed. Next, given the use of second-order constructs in this research model, an assessment of the proposed secondorder models for the PQ and the whole measurement model was adapted from the recent business research literature (Di-Clemente et al, 2019;Ketkaew et al, 2019Ketkaew et al, , 2020Nadeem et al, 2020). Explicitly, perceived service quality was assigned as a second-order construct, suggesting the two-step approach to assess the study's measurement model (first-order and second-order measurement models) and the full structural model.…”
Section: Discussionmentioning
confidence: 99%